The politics of refuge: sanctuary cities, crime, and undocumented immigration - O'Brien, Benjamin Gonzalez; Collingwood, Loren; El-Khatib, Stephen Omar (2019)
This article assesses the claim that sanctuary cities$1 (Bdefined as cities that expressly forbid city officials or police departments from inquiring into an individual$1 (Bs immigration status$1 (Bare associated with post hoc increases in crime. We employ a causal inference matching strategy to compare similarly situated cities where key variables are the same across the cities except the sanctuary status of the city. We find no statistically discernible difference in violent crime, rape, or property crime rates across the cities. Our findings provide evidence that sanctuary policies have no effect on crime rates, despite narratives to the contrary. The potential benefits of sanctuary cities, such as better incorporation of the undocumented community and cooperation with police, thus have little cost for the cities in question in terms of crime. - Reproduced.s
Keywords: Crime; Sanctuary cities